Employer aversion to criminal records: An experimental study of mechanisms - Sugie, Naomi F. (Criminology, 2020)
The mark of a criminal record is clearly harmful for employment. The reasons for employer aversion, however, are not well established even though legal, policy, and scholarly responses rely on particular explanations. We propose that explanations for aversion often fit under a repetition risk framework in which employers use records as neutral sources of information about prior illegal activity and make decisions to minimize risk of similar future conduct. A second explanation is stigma, in which the records themselves, independent of conduct, trigger stereotypes, status loss, and discrimination. Using an experimental employer survey, we find that employers evaluate applicants with records more negatively than they do applicants with similar behavior signaled through non-criminal-justice sources (e.g., social media); this effect remains after accounting for predictions about future conduct. It is also most apparent among higher status jobs rather than among manual labor jobs, and it persists after adjusting for firm-level and legal constraints. We conclude that aversion reflects not only repetition risk but also the stigma of criminal justice contact. Insofar as criminal record screening is not exclusively a form of rational risk management, this finding may lead to altered assessments of the benefits of screening relative to the costs of perpetuating inequality produced by the criminal justice system.